General Scheme for Oxidative Quenching of a Copper Bis‐Phenanthroline Photosensitizer for Light‐Driven Hydrogen Production. Issue 13 (25th May 2016) - Windisch, J.; Orazietti, M.; Hamm, P.; Alberto, R.; Probst, B.
Abstract: A new, general reaction scheme for photocatalytic hydrogen production is presented based on oxidative quenching of a homoleptic copper(I) bis‐1, 10‐phenanthroline photosensitizer (PS) by 1‐methyl‐4‐phenyl‐pyridinium (MPP + ) as the electron relay and subsequent regeneration of the so formed copper(II) complex by a sacrificial electron donor. Electron transfer from the relay to various cobalt based water reduction catalysts and subsequent H2 production was shown to close the catalytic cycle. Transient absorption experiments unambiguously confirmed the proposed pathway, both the oxidative quenching and subsequent regeneration of oxidized PS. Photocatalytic test runs further confirmed the role of MPP + and up to 10 turnovers were achieved in the relay. The performance limiting factor of the system was shown to be the decomplexation of the copper PS. Quantum yields of the system were 0.03 for H2 production, but 0.6 for MPP . formation, clearly indicating that unproductive pathways still prevail. Abstract : Changing the direction ! Oxidative quenching of a homoleptic copper phenanthroline photosensitizer enables a very general scheme for photocatalytic proton reduction. 1‐Methyl‐4‐phenylpyridinium serves as a reversible electron relay between the excited copper dye and several water reduction catalysts. The oxidized copper dye is subsequently regenerated by a sacrificial agent to close the catalytic cycle.